A facile and mild one-pot process for direct extraction of lipids from wet energy insects of black soldier fly larvae. (March 2020) - Feng, Weiliang; Xiong, Huan; Wang, Weiguo; Duan, Xiaoling; Yang, Tong; Wu, Cheng; Yang, Fang; Wang, Teilin; Wang, Cunwen
Abstract: The insect lipids were recovered using one-pot manner via a high speed homogeniser from the wet black soldier fly larvae as the novelty lipid feedstocks at room temperature and pressure in this study. The comparison of the influences of different conditions (solvent types, solute-solvent ratios, water contents, and homogenization intensities) on the lipid extraction efficiency and lipid compositions were studied and evaluated. The results indicated that all the binary solvents tested in this work present a higher extraction capacity (70–74%) than the monophasic solvent increasing two-fold the lipid extraction yield. There was a significant difference between the 30.96% and 86.67% in saponifiable lipids purity for different extraction solvent systems. The effects of water contents on the lipid extraction process for relatively low contents of non-polar solvent in the binary extraction solvents system were greater than that of high contents of non-polar solvent. However, fatty acid methyl esters profiles from the energy biomass indicate that relevant fatty acids were present in all solvent extracts, with no significant variation in the FAME composition provided for different investigated conditions. Key characteristics of the recovered lipids indicate that the pretreatment process-cell disruption was a critical step in the recovery of intracellular lipids from the wet biomass, which significantly enhancing the lipid extraction process. In combination with SEM images of the damaged cells, the precise mechanism of cell disruption via the high speed homogeniser was comprehensively described. At last, the kinetic model (r 2  ≥ 0.9937) of lipid extraction from the ruptured cell at various homogenization intensities (6000–14000 rpm) was explored in preliminary. The extraction constants were determined for the lipid extraction process, ranging from 0.0531 to 0.0681 s −1 . Considering its energy-efficiency and potential for scale-up, the one-pot manner may be a promising method to achieve industrial-scale lipid extraction from wet biomass. Highlights: Lipid extraction from wet biomass was successful using an one-pot technique. Effect of operating parameters on the lipid extraction process was studied. The lipid extraction efficiency reached 75.92% under defined extraction condition. The kinetics model of lipids extraction from the ruptured insect cells was explored. The novel method has the merits of low temperature, low pressure, and short time.